2001
DOI: 10.1097/00005768-200102000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in physical activity levels of young adults

Abstract: Promoting walking and various forms of moderate-intensity physical activities to young adult males, and encouraging young adult females to adopt other forms of moderate-intensity activity to complement walking may help to ameliorate decreases in physical activity over the adult lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 0 publications
8
65
1
4
Order By: Relevance
“…Therefore, public health policies may need to focus on encouraging younger adults, especially females, to participate in vigorous physical activity. Consideration needs to be given as to how to provide opportunities for participation by older adults that will replace those offered by school and club sport structures during the school and the young adult years (14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, public health policies may need to focus on encouraging younger adults, especially females, to participate in vigorous physical activity. Consideration needs to be given as to how to provide opportunities for participation by older adults that will replace those offered by school and club sport structures during the school and the young adult years (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the PA literature, studies indicated a decrease in physical activity as people get older (Mullineaux et al, 2000;Aktener et al, 2006), especially moving from adolescence to adulthood seems to be an identical time span for the decline in exercise level (Leslie et al, 2001;Kin-İsler et al, 2009). PA behavior has been linked with an increased likelihood of the more educated to be physically active (Dishman, et al, 1985).…”
mentioning
confidence: 99%
“…Unfortunately, physical activity levels tend to decline during the transition from high school to college, especially among women. [2][3][4][5] Increasing daily walking can have lasting health benefits for collegeaged women. 6 Without intervention, the declines in physical activity observed from high school to college will likely continue into adulthood, placing these individuals at increased risk for health detriments related to physical inactivity including coronary heart disease, type 2 diabetes, breast cancer, and colon cancer.…”
mentioning
confidence: 99%